(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The rapid development of artificial intelligence technologies has significantly transformed contemporary English vocabulary. Terms that were previously restricted to specialized scientific and technological discourse are increasingly becoming part of everyday communication. This linguistic phenomenon, known as determinologization, reflects the transition of technical terms into general language use. The present study examines the determinologization of AI-related terms in modern English and explores their semantic, functional, and pragmatic transformations in digital discourse.